2003
DOI: 10.1111/j.1550-7408.2003.tb00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Isospora belli Infection: Observation of Unicellular Cysts in Mesenteric Lymphoid Tissues of a Brazilian Patient with AIDS and Animal Inoculation

Abstract: We describe the finding of unizoic cysts of Isospora belli in lymphoid tissues of a Brazilian patient with AIDS, and discuss the possibilities of their drug resistance, they being the cause of relapses, and of being an indication for the existence of intermediary or paratenic animal hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…This observation is in line with that made on black siskins by Giacomo et al (1997). Susceptibility to infection may be associated with decreased immune responsiveness (Certad et al, 2003;Frenkel et al, 2003) and/or long distance migrations of these animals (Giacomo et al, 1997). Since sparrows are one of the most common birds to live in close association with humans, Isospora spp.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…This observation is in line with that made on black siskins by Giacomo et al (1997). Susceptibility to infection may be associated with decreased immune responsiveness (Certad et al, 2003;Frenkel et al, 2003) and/or long distance migrations of these animals (Giacomo et al, 1997). Since sparrows are one of the most common birds to live in close association with humans, Isospora spp.…”
supporting
confidence: 86%
“…Isospora spp. infections have also been observed in pigs (Bach et al, 2003), dogs (Ho et al, 2006) and cats (Huh et al, 1993) as well as in humans (Certad et al, 2003;Frenkel et al, 2003). Previous studies have indicated that sparrows parasitised by Isospora spp.…”
mentioning
confidence: 98%
“…Although in that study it was not possible to correlate the restriction profiles with the clinical manifestations of the patients, the results obtained demonstrate the occurrence of different genotypes infecting humans and open perspectives for the discovery of different routes of transmission of cystoisosporosis. FRENKEL et al 9 suggested a facultatively heteroxenous life cycle for this species, with the formation of extraintestinal tissue cysts in intermediate and/or paratenic hosts. As observed for cryptosporidiosis, the presence of anthropozoonotic transmission would explain the presence of this infection in areas with good sanitary conditions.…”
mentioning
confidence: 95%
“…Although the adherence to therapy could be questioned in some patients, it was excellent in others who were under direct observed therapy. As exogenic reinfestation is probably very rare in France, endogenic reinfestation could be suspected in some of these patients, because of the persistence of intraenterocyte merozoites, and potential extra-intestinal locations of the parasite on which anti-infectious treatment could be less effective [21,22]. Another explanation could be the selection of resistance to cotrimoxazole, but this hypothesis could not be tested as I. belli cannot be cultivated in vitro and has not yet been sequenced.…”
Section: Discussionmentioning
confidence: 99%